Planning, teaching methodologies and experimentation in sciences in the context of online classes in the licensing in biological sciences (Revista Contexto & Educação, 2023)
Abstract: The study reported in this article aims to understand the transformations of Science and Biology undergraduates' conceptions about Science teaching methodologies and the possibilities for reinventing online class planning in the process of Research-Formation-Action in Science in the initial formation of teachers. This research presents a qualitative and documentary approach, having as instruments of data collection written narratives of formation diaries of 14 undergraduate students in Biological Sciences, atending the subject Practical as Curricular Component III. The analysis of the research was carried out from the Textual Discursive Analysis and followed the steps of unification, categorization and communication. Two reflective spirals emerged from the ATD: a) Interweaving the threads of reflections on Science teaching plans and methodologies; and b) Reflections on the challenges of the Covid-19 Pandemic: necessary (trans) formation. Through the constitution of this mosaic, we realized that, as the undergraduates plan the classes and think about the methodologies in PeCC III, their understandings emerge in another landscape, revealing the experience of knowledge in teaching.